BcRPD3-Mediated Histone Deacetylation Is Involved in Growth and Pathogenicity of Botrytis cinerea - Zhang, Ning; Yang, Zhenzhou; Zhang, Zhonghua; Liang, Wenxing (Frontiers in Microbiology, 2020)
Histone deacetylase activity plays an important role in transcriptional repression. Botrytis cinerea is an important necrotrophic fungal pathogen distributed worldwide and parasites a wide range of hosts. However, the molecular mechanisms of how B. cinerea regulates growth and host infection remain largely unknown. Here, the function of BcRPD3, a histone deacetylase of B. cinerea, was investigated. Overexpression of the BcRPD3 gene resulted in significantly decreased acetylation levels of histone H3 and H4. The BcRPD3 overexpression strains showed slightly delayed vegetative growth, dramatically impaired infection structure formation, oxidative stress response, and virulence. RNA-Seq analysis revealed that enzymatic activity related genes, including 9 genes reported to function as virulence factors, were downregulated in BcRPD3 overexpression strain. Chromatin immunoprecipitation followed by qPCR confirmed the enrichment of BcRPD3 and H3Kac at the promoter regions of these nine genes. These observations indicated that BcRPD3 regulated the transcription of enzymatic activity related genes by controlling the acetylation level of histones, thereby affecting the vegetative growth, infection structure formation, oxidative stress response, and virulence of B. cinerea.